Gas flows in a changing-look AGN. Issue Volume 15:Issue S359(2020) (March 2019) - Raimundo, Sandra I.
Abstract: The galaxy Mrk 590 is one of the few known 'changing-look' Active Galactic Nuclei (AGN) to have transitioned between states twice, having just increased its flux after a period of ˜10 years of low activity. In addition to the increase in flux, the optical broad emission lines have reappeared but show a different profile than what was observed before they disappeared. The gas motions in the host galaxy of this changing-look AGN show outflows and dynamical structures able to drive gas to the nucleus, suggesting an interplay between inflow and outflow in the centre of the galaxy.